The Effectiveness of Using Reality Augmented Media to Increase The Students’ Learning Motivation in Chemical Bonding Material - Nurillah, Happy Sagita; Purwanto, Kriesna Kharisma; Fatayah, Fatayah (Tarbiyah : Jurnal Ilmiah Kependidikan, 2022)
The purpose of this study was to determine the effectiveness of using Augmented Reality media to increase student learning motivation. This type of research is a quantitative quasi-experimental design with Pretest-Posttest Non-Equivalent Control Group Design. The sample in this study were 42 students in class X-Natural Science and X-Social Science. The research instrument used was a motivational questionnaire with 4 indicators, namely Attention, Relevance, Confidence, Satisfaction (ARCS). Data collection techniques were carried out by giving motivational questionnaires to students before and after learning. The data that has been obtained, then analyzed using the completeness formula of student achievement to determine the level of effectiveness of Augmented Reality media on student learning motivation. The results of the effectiveness of the media in the experimental class and the control class obtained the final motivational completeness percentages of 100% and 86%, respectively. Based on the results of the effectiveness of the media, it can be concluded that the use of Augmented Reality media is stated to be very effective for increasing student motivation in chemical bonding material.